Dry adhesives from carbon nanofibers grown in an open ethanol flame - Lutz, Christian; Syurik, Julia; Shyam Kumar, C. N.; Kübel, Christian; Bruns, Michael; Hölscher, Hendrik (Beilstein Journal of Nanotechnology, 2017)
Based on magnetic-field-assisted growth of carbon nanofibers in an open ethanol flame we fabricated arrays of carbon nanofibers with different degrees of orientation. Inspired by the dry adhesive system of geckos we investigated the adhesive properties of such carbon nanofiber arrays with ordered and random orientation. AFM-based force spectroscopy revealed that adhesion force and energy rise linear with preload force. Carbon nanofibers oriented by a magnetic field show a 68% higher adhesion (0.66 N/cm2) than the randomly oriented fibers. Endurance tests revealed that the carbon nanofiber arrays withstand 50.000 attachment/detachment cycles without observable wear.
Keywords: adhesion; atomic force microscopy; carbon nanofibers